Creative and critical thinking: independent or overlapping components? - Wechsler, Solange Muglia (2018)
There are questions as to whether creative or critical thinking are relevant for problem solving. Therefore, we have analyzed the association between creative and critical thinking to determine whether their components are independent or associated with each other. A sample of 291 undergraduate students from Brazil (41.2%) and Spain (58.8%), with ages ranging from 17 to 56 years (M = 21.35, SD = 5.61), from both genders (84% women), answered two creative and critical thinking online tests. Two models were tested using the Structure of Equation Modeling, the first indicating that creativity and critical thinking converge for a general single factor, and the second indicating that they are two separate factors, even if moderately correlated. The results demonstrated that the second model has the best fit indexes, thus confirming the independence of each cognitive component in reference to critical thinking and creativity. In conclusion, the results suggest the need to enhance both skills for developing problem solving abilities.